1992
DOI: 10.4141/cjas92-047
|View full text |Cite
|
Sign up to set email alerts
|

The effect of organic acids and enzyme supplementation on the performance of pigs fed barley-based diets

Abstract: J. 1992. The effect of organic acids and enzyme supplementation on the performance of pigs fed barley-based diets. Can. J. Anim. Sci. 72: 395-402. Two factorial design experiments (sex X treatment) were conducted to determine the efficacy of enzyme and organic acid supplementation on improving the nutritive value ofbarley-based diets for both starter and finisher pigs. for exp. 1, 48 crossbred growing pigs (25.1 + 2.8 kg) were fed either a barleybased controi diet or a similar diet supplemented wtth0.25% enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 12 publications
4
16
1
2
Order By: Relevance
“…p-Glucan is also highly digestible in the ileum of pigs (Graham et al 1986), apparently more digestible than starch (Graham et al 1989) (Thacker et al 1988(Thacker et al , 1992b (Thacker et al , 1992a It seems that the most likely application would be in weanling pig diets where pancreatic enzyme production may be limiting (Lindemann et al 1986), which is consistent with industry practice. One final point to note is that most research trials have been conducted with older pigs.…”
Section: Pentosans As Growth-depressantssupporting
confidence: 52%
See 1 more Smart Citation
“…p-Glucan is also highly digestible in the ileum of pigs (Graham et al 1986), apparently more digestible than starch (Graham et al 1989) (Thacker et al 1988(Thacker et al , 1992b (Thacker et al , 1992a It seems that the most likely application would be in weanling pig diets where pancreatic enzyme production may be limiting (Lindemann et al 1986), which is consistent with industry practice. One final point to note is that most research trials have been conducted with older pigs.…”
Section: Pentosans As Growth-depressantssupporting
confidence: 52%
“…One final point to note is that most research trials have been conducted with older pigs. In studies with weaniing pigs fed barley, both daily gain and feed conversion were moderately improved (but not significantly) with enzyme treatment (Thacker et al 1992b) and in one case a reduction in post-weaning diarrhoea was reported (Inborr and Ogle 1988 Slominski and Campbell (1990) did observe improved digestibility of the nonstarch polysaccharides of canola meal with enzyme supplementation (multi-activity). (Jacorzynski 1987).…”
Section: Pentosans As Growth-depressantsmentioning
confidence: 99%
“…Attempts have been made to improve the performance of pigs fed barley through enz).rne supplementation. However, supplementation of barley-based diets with B-glucanase have not produced improvements in pig performance comparable to those observed with poultry (Thacker et al 1988(Thacker et al ,1992a.…”
Section: Canadian Journal Of Animal Sciencementioning
confidence: 99%
“…* References: Kirchgessner & Roth-Maier, 1975;Kirchgessner & Roth, 1976, 1978a, 1987a, b, 1990Falkowski & Aherne, 1984;Giesting & Easter, 1985, 1991Broz & Schulze, 1987;Bolduan et al 1988a,b;Risley et al 1991;Eckel et al 1992a;Eidelsburger et al 1992b,d;Kirchgessner et al 1993Kirchgessner et al , 1997Krause et al 1994;Paulicks et al 1996;Roth et al 1996. { References: Thacker & Bowland, 1980;Thacker et al , 1992, 1989Petersen & Oslage, 1982a;Schulz & Oslage 1982;Giesting & Easter, 1985;Baustad, 1993;Kirchgessner et al 1997;…”
Section: Weaned Pigletsunclassified